Fecal HMGB1 Reveals Microscopic Inflammation in Adult and Pediatric Patients with Inflammatory Bowel Disease in Clinical and Endoscopic Remission. Issue 12 (December 2016) - Palone, Francesca; Vitali, Roberta; Cucchiara, Salvatore; Mennini, Maurizio; Armuzzi, Alessandro; Pugliese, Daniela; D'Incà, Renata; Barberio, Brigida; Stronati, Laura
Abstract : Background: Fecal high mobility group box 1 (HMGB1) has been suggested to be a novel noninvasive biomarker of gut inflammation. We aimed to assess the reliability of fecal HMGB1, compared with fecal calprotectin (FC), in detecting intestinal inflammation in pediatric and adult patients with inflammatory bowel disease (IBD) and to evaluate the accuracy of HMGB1 in identifying patients with IBD in clinical and endoscopic remission who still have histologic features of inflammation. Methods: Stool samples from 85 children with IBD (49 Crohn's disease [CD] and 36 ulcerative colitis [UC] and 119 adults [57 Crohn's disease and 62 ulcerative colitis]) were analyzed for the study. Age-matched healthy subjects were used as controls. Fecal HMGB1 and fecal calprotectin were detected through western blot and ELISA, respectively. Results: Fecal HMGB1 expression was significantly increased in pediatric and adult patients with Crohn's disease and ulcerative colitis and strongly correlated with the disease severity. Fecal calprotectin and HMGB1 significantly correlated in pediatric (r: 0.60, P < 0.001) and adult (r: 0.72, P < 0.001) IBD patients. Moreover, in patients with clinical and endoscopic remission only fecal HMGB1 showed a strong match with the degree of histological scores of inflammation (CGHAS/IGHAS for Crohn's disease and Geboes Score for ulcerative colitis). Conclusions: Fecal HMGB1 is confirmed to be a reliable biomarker of intestinal inflammation; indeed, it significantly correlates with fecal calprotectin in pediatric and adult IBD patients. Moreover, only fecal HMGB1 identifies histologic inflammation in subjects with IBD in clinical and endoscopic remission. Abstract : Article first published online 13 October 2016.